Peta Mata Pelajaran Agama Dalam Pendidikan Nasional - Ahmad Darlis; Ahmad Ridho; Adhelia Ferari ; Mhd Rifqih Fernanda; Rizka Ardiyanti (Fakultas Tarbiyah IAI Nasional Laa Roiba, 2023)
Everyone should pursue their education. The nation will also grow through education. In Indonesian education, the term